ROOM OPTIMIZATION IN COURSE SCHEDULING USING THE GREEDY ALGORITHM - JONAS FRANKY RUDIANTO PANGGABEAN; KAMSON SIRAIT (Jurnal Mantik, 2022)
Greedy algorithm is an algorithm that solves problems with systematic steps. In this research, the optimization used is the use of existing rooms on the AMIK Medicom Medan campus. The problem that often occurs on campus is the scheduling of courses with limited space. With these problems, it can hamper various other activities and the time needed is quite long to arrange a schedule because it is done manually. The purpose of this research is to test the greedy algorithm in optimizing empty spaces in the manufacture of the Course Scheduling System and to compare the algorithm testing with manuals. The application of the algorithm to the system will produce an effective course schedule without any problems in the use of the room so that there is no simultaneous use of the room in other courses.